2014
DOI: 10.1080/08841241.2014.972486
|View full text |Cite
|
Sign up to set email alerts
|

Student-customer orientation at a higher education institution: the perspective of undergraduate business students

Abstract: Existing literature is polarized and primarily conceptual on the topic of student-customer orientation. Research into this phenomenon has failed to realize that higher education as such consists of several different educational experiences and has therefore addressed and studied the issue at too general a level, i.e. at the level of the higher education institution (HEI) as a whole, not at the level of educational experiences that an HEI provides. Based on a validated model of educational experiences, validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…To conduct research activities, facilities and study opportunities have been appropriately granted to students resulting in high reliability among students as university customers. These results were consistent with the findings of the studies by Koris et al, (2015), Saunders (2014) and Sahney (2016).The findings regarding the content component revealed that students were satisfied with the appropriate presentation of the content-oriented theoretical training programs designed by the group to attract customers in higher education and were able to succeed in this regard. In connection with another customer-oriented structure in higher education, the findings also showed that change in faculty attitudes in favor of customer was at the optimum level and the management support of the creativity and achievements of the students accompanied by financial and scientific support of the faculty have been evaluated at a desirable level.…”
Section: -Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To conduct research activities, facilities and study opportunities have been appropriately granted to students resulting in high reliability among students as university customers. These results were consistent with the findings of the studies by Koris et al, (2015), Saunders (2014) and Sahney (2016).The findings regarding the content component revealed that students were satisfied with the appropriate presentation of the content-oriented theoretical training programs designed by the group to attract customers in higher education and were able to succeed in this regard. In connection with another customer-oriented structure in higher education, the findings also showed that change in faculty attitudes in favor of customer was at the optimum level and the management support of the creativity and achievements of the students accompanied by financial and scientific support of the faculty have been evaluated at a desirable level.…”
Section: -Discussionsupporting
confidence: 89%
“…This suggests that how people approach their time as students is more complex than some of the literature assumes. In another study, Koris et al, (2015) reviewed student-customer orientation at a higher education institution: the perspective of undergraduate business students based on a validated model of educational experiences. The results of the study show that students expect to be treated as customers in some, but not all categories of educational experience that an HEI offers.…”
Section: -Introductionmentioning
confidence: 99%
“…After all, students are paying for a service in the form of a degree-level education, although it is not a straightforward transaction of buying a product or service with a promised purpose or outcome since students are still expected to earn their qualifications through individual merit. Yet, universities and staff are also expected to do more and ensure students feel that their degrees are good "value for money" (Koris et al 2015;Woodall, Hiller, and Resnick 2014). Given the high tuition fees, the worthwhileness of a degree can often be interpreted through their exchange and symbolic values, especially privileged access into particular employment or further study.…”
Section: Teaching In Higher Educationmentioning
confidence: 99%
“…Good brands are the key resources for creating a competitive advantage (Aaker, 1996) of all organizations, including higher education institutions. Higher education is a complex system, with 11 different types of experiences, including students' feedback, graduation, curriculum design, communication with the service staff, grading, classroom behavior, classroom studies, individual studies, teaching methods and a course design (Koris et al, 2015).…”
Section: The Concept Of Branding In Higher Educationmentioning
confidence: 99%